2001
DOI: 10.1046/j.1365-2494.2001.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Bite dimensions for cattle grazing herbage at low levels of depletion

Abstract: The processes that occur during the depletion of a single feeding station by grazing cattle are important to our understanding of intake at larger spatial scales. Factorial experiments were conducted in which feeding stations of different sizes were grazed individually by cattle to various levels of depletion, defined as the number of bites removed. Feeding stations in Experiment 1 (alfalfa) measured 0·11, 0·24 and 0·45 m2, and the numbers of bites removed for depletion levels 1–3 were 35, 70 and 104 m−2 respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…In vegetative swards, bite area was not related to sward height which disagrees with previous studies where bite area increased with sward height (Cangiano et al, 2002;Flores et al, 1993;Laca et al, 1992;Ungar et al, 2001). In tall swards the animal can fully exploit the benefits of the tongue sweep movements to gather forage and thus the animal can achieve the maximum bite area.…”
Section: Bite Dimensions and Selectivity Regulationcontrasting
confidence: 92%
See 1 more Smart Citation
“…In vegetative swards, bite area was not related to sward height which disagrees with previous studies where bite area increased with sward height (Cangiano et al, 2002;Flores et al, 1993;Laca et al, 1992;Ungar et al, 2001). In tall swards the animal can fully exploit the benefits of the tongue sweep movements to gather forage and thus the animal can achieve the maximum bite area.…”
Section: Bite Dimensions and Selectivity Regulationcontrasting
confidence: 92%
“…The lack of response of bite area to sward height in vegetative swards in the current work can be explained in part by the relatively small body mass of the animals used in this experiment, whose bite area is less sensitive to the increase in sward height than that of bigger animals (Gordon 1987), and by the significant correlation between sward height and grazing resistance (r = 0.88, P b 0.001). Therefore, the positive relationship between bite area and sward height (Cangiano et al, 2002;Flores et al, 1993;Laca et al, 1992;Ungar et al, 2001) could have been compensated by the negative relationship between bite area and sward grazing resistance (Illius et al, 1995) resulting in the observed lack of effect of sward height on bite area of the current experiment.…”
Section: Bite Dimensions and Selectivity Regulationmentioning
confidence: 82%
“…Selective grazing occurs where, independently of pasture condition, cattle prefer the more nutritious and easily ingested top stratum of the pasture before consuming the lower strata that impose a greater restriction on bite dimensions, have a lower diet quality and thus lower potential intake rate (Chacon and Stobbs, ; Hendricksen and Minson, ; Ungar and Ravid, ; Ungar et al ., ). We hypothesize that daily forage intake and diet quality would significantly decrease when the top grazing stratum is removed across the entire area of the pasture.…”
Section: Introductionmentioning
confidence: 97%
“…We hypothesize that daily forage intake and diet quality would significantly decrease when the top grazing stratum is removed across the entire area of the pasture. While some studies have measured the level of depletion of grazing strata at the feeding‐station level (Ungar and Ravid, ; Ungar et al ., ), the extrapolation of the results of these studies to the paddock level is limited by the ability of the animals to compensate for a reduction in instantaneous intake rate by increasing grazing time. Despite previous studies on tropical pastures demonstrating the effect of green leaf herbage mass on forage intake at the paddock level (Chacon and Stobbs, ; Hendricksen and Minson, ), there are no measurements of the level of depletion of the grazing strata.…”
Section: Introductionmentioning
confidence: 99%
“…Wade, ; Carrere et al ., ; Cangiano et al ., ; Benvenutti et al ., ; Goncalves et al ., ). The bite area is reduced as the sward is grazed down because of access to parts of the plant with a higher proportion of stems (Ungar et al ., ). Therefore, the bite mass decreases as the sward height is grazed down because of the combination of a smaller bite area (Ungar et al ., ) and reduced absolute bite depth (Laca et al ., ; Benvenutti et al ., ).…”
Section: Introductionmentioning
confidence: 97%